The Problems of Formation of Communicative Competence of Higher Educational Institutions Students - Tashmatova Madina Abdukarimovna (Genius Journals, 2022)
The article under discussion reveals the formation of communicative competence of students in non-linguistic higher educational institutions. The role and aspects of learning English in a technical university based on the concept of competence approach and in the context of multi-disciplinary education had been analyzed. The author considers some methodological principles and peculiarities of teaching a foreign language in a technical university, based on the criteria of professional competence development.
Keywords: speech activity; academic mobility; competence; technology